Neurolaryngology - Sataloff, Robert Thayer; Sataloff, Robert Thayer; Sataloff, Robert Thayer (Plural Publishing, 2017)
Neurolaryngology brings together in one volume the latest concepts in this important and developing field. In order to make this text as useful as possible for clinicians, selected chapters on general concepts important to clinical care have been included, including chapters on history, physical examination, clinical voice laboratory assessment, common diagnoses and treatments, and other topics important to all voice patients, including those with neurolaryngological complaints.